Subjective assessment of mood in patients hospitalized in forensic psychiatry departments - Fojcik, Joanna; Górski, Michał; Skowronek, Rafał; Szawarnoga, Daniel; Krzystanek, Marek (Frontiers in Psychiatry, 2025)
ObjectiveSubjective mood assessment is a crucial element in the diagnostic and therapeutic process in psychiatry. Assessment of subjective mood is particularly important among forensic psychiatric patients. This population is characterized by specific environmental factors—isolation, limited autonomy, and stress related to legal proceedings. This situation can significantly impact patients’ well-being and mood. The aim of this study is to discuss the specificity of subjective mood assessment in the forensic psychiatric patient population and the importance of this tool in everyday clinical practice.Material and methodsThe study was conducted in forensic psychiatry departments under basic security conditions using a survey method among 112 patients. The research tool included a research questionnaire with a demographic and clinical survey and the Beck Depression Inventory.ResultsThe overall level of depressive symptoms among patients was relatively low. The highest symptom severity was associated with feelings of guilt, loss of interest, and pessimism. The analysis revealed a significant correlation between the length of hospitalization and the level of depression – the longer the stay, the higher the mean scores on the Beck Depression Inventory (p = 0.00001). The highest values were observed among patients hospitalized for 5 to 9 years.ConclusionsThe analysis shows that patients in forensic psychiatry wards have a low level of depressive symptoms, but their severity increases with the length of stay.